Rating economy of conversion of the fuel supply system from VE to the VE-EDC - Lý Vĩnh Đạt; Trần Anh Tuấn (Journal of Technical Education Science, 2014)
The emission and noise in Diesel engines are the main factors that cause the environmental pollution. To overcome the disadvantages, the Electronic Diesel Control system (EDC) has been equipted in modern Diesel engines. The paper study the installing and converting the conventional VE fuel system to VE - EDC in Hyundai H100 1T25. The applying of VE - EDC in traditional Diesel engine brings some advantages about performance, efficiency, emission and fuel consumption due to the controlling exactly of fuel flow and injection timing which are controlled by spill control and timing control valves, respectively. The results show that the engine performance is significantly increased (about 5 ÷10 % for torque and 10 ÷15 % for power), the fuel consumption is also reduced about 10 ÷30 % when using VE - EDC for the conventional Diesel engine. In additional, the improving of emission in engine also achieve: the reducing of CO about 40 ÷50 % and HC about 5÷20%.